Aerobic Capacity as a Mediator of the Influence of Birth Weight and School Performance - Garcia-Hermoso, A (Cambridge University Press, 2016)
Low birth weight is associated with cognitive impairments persisting into adolescence and early adulthood. The purposes of this study was two-fold: to analyse the association between birth weight (BW) and school performance, and to determine the influence of adolescent aerobic capacity and muscular strength on the association between BW and school performance in children at 12-13 years. The study included 395 children (50.4% boys, aged 12-13 years). Self-reported BW was evaluated. We measured school performance (mean of the grades obtained in language and mathematics) and two physical fitness tests (aerobic capacity and muscular strength). Analysis of variance was used to analyse the differences in school performance according to BW categories (≤2500, 2500-3500 and ≥3500 g). Linear regression models fitted for mediation analyses examined whether the association between BW and school performance was mediated by aerobic capacity and/or muscular strength. Higher BW was associated with better school performance independent of current body mass index. These differences disappeared after controlling for aerobic capacity, which also mediated the association between BW and school performance (13.4%). The relationship between BW and school performance seems to be dependent on aerobic capacity fitness. Our results are of importance because the consequences of BW tend to continue into childhood, and current physical fitness of the children may potentially be modified to improve school performance. © Cambridge University Press and the International Society for Developmental Origins of Health and Disease 2016.